Media Pembelajaran Stocklab Berbasis Multimedia - Muhatri, M (STIKOM Tunas Bangsa Pematangsiantar, 2020)
This study aims to develop multimedia-based learning media for StockLab; StockLab games are generally played by 3 to 5 people. This game is often played by students at the Faculty of Economics and Business as a simulation medium in building stocks where the card introduces investment, stocks, and the capital market. Stockland is a game using card media such as playing, domino or Uno with game instructions such as players must compete with each other to develop assets by investing in various sectors of stocks and mutual funds, and can take various actions optimally to become an investor with the most coins at the end of the game.